Perspective on the Recent Measurements of Reduced Nitrogen Compounds in the Atmosphere - Lee, S.-H. (Frontiers in Environmental Science, 2022)
Reduced-nitrogen compounds (RNC), such as ammonia and amines, play important roles in atmospheric aerosol nucleation, secondary organic aerosol (SOA), and cloud formation processes. Fast measurements of ammonia and amines are made with a chemical ionization mass spectrometer (CIMS). Clusters containing RNC are measured with an atmospheric pressure interface time of flight mass spectrometer (APi-TOF) or chemical ionization APi-TOF (CI-APi-TOF). Aerosol-phase amines can be detected with a single particle mass spectrometer at real-time, or with offline chemical analytical methods using filter samples. However, the application of these instruments in real atmospheric measurements is still very limited. This perspective article highlights recent measurements of RNC in the atmosphere and discusses their implications in new particle formation (NPF).